2022
DOI: 10.1186/s40001-022-00892-9
|View full text |Cite|
|
Sign up to set email alerts
|

Regimen comprising GLP-1 receptor agonist and basal insulin can decrease the effect of food on glycemic variability compared to a pre-mixed insulin regimen

Abstract: Background Increasing evidence suggests that glucagon-like peptide 1 (GLP-1) receptor agonists (RA) can stabilize glycemic variability (GV) and interfere with eating behavior. This study compared the impact of insulin, GLP-1 RA, and dietary components on GV using professional continuous glucose monitoring (CGM). Methods Patients with type 2 diabetes underwent CGM before and after switching from a twice-daily pre-mixed insulin treatment regimen to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Cell Viability. Cell viability was reduced in the high fatgroup (average SI = 2:70) relative to the control group (average SI = 2:17) (2:17 ± 0:06 vs. 2:70 ± 0:08, P < 0:01), of the 10LR group (average SI = 2:63) did not differ from the high-fat group (2:63 ± 0:12 vs. 2:70 ± 0:08, P > 0:05), but both the 100LR (average SI = 2:64) and 1000LR (average SI = 2:50) groups had higher cell viability (P < 0:01) [10,11]. Cell viability highest in the 100LR group (P < 0:05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Viability. Cell viability was reduced in the high fatgroup (average SI = 2:70) relative to the control group (average SI = 2:17) (2:17 ± 0:06 vs. 2:70 ± 0:08, P < 0:01), of the 10LR group (average SI = 2:63) did not differ from the high-fat group (2:63 ± 0:12 vs. 2:70 ± 0:08, P > 0:05), but both the 100LR (average SI = 2:64) and 1000LR (average SI = 2:50) groups had higher cell viability (P < 0:01) [10,11]. Cell viability highest in the 100LR group (P < 0:05).…”
Section: Resultsmentioning
confidence: 99%
“…The high-fat and LR-intervention groups were cultured in MEM supplemented with PA at 0.6 mmol/L. The medium of the LR-intervention groups was additionally supplemented with LR at 10 nmol/L (10LR), 100 nmol/L (100LR), or 1000 nmol/L (1000LR) [10][11][12].…”
Section: Cellmentioning
confidence: 99%
“…Wang et al measured average TBR < 3.9 mmol/l of 9.4% for a premixed insulin group ( n = 194) [ 26 ], and Margaritidis et al the value of 6.3% in a well-controlled group ( n = 36) [ 27 ]. Lin et al reported a TBR value of 0 for their 16 premix patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed a similar TIR of 59.8% for their group [ 26 ]. Lin et al reported a TIR of 39.0% for premix-treated patients [ 29 ], and Margaritidis et al measured a value of 74.2% [ 27 ]. The TAR target for high-risk people was met in 77% of our group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation